PALEOBATHYMETRIC INTERPRETATION OF THE FISH OTOLITHS FROM THE LOWER - MIDDLE QUATERNARY DEPOSITS OF KEPHALLONIA AND ZAKYNTHOS ISLANDS (IONIAN SEA, WESTERN GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
Fish otoliths are herein used to estimate the depositional depth of the Early - Middle Pleistocene deposits at SE Zakynthos and SW Kephallonia Islands (Ionian Sea, Western Greece), through comparison with the modern bathymetric distributions of the identified fish taxa. These estimates provide a more detailed picture of the depth variations for the Gelasian - Ionian stage interval in the study areas. The Lower Pleistocene marine deposits of the Gerakas Formation (SE Zakynthos Island, Ionian Sea) were deposited at average depths of 400-450 meters, with eustacy playing an important role in the depth variability, between 1.95-1.73 Ma. An uplifting episode, followed by subsidence takes place between 1.73-1.66 Ma, taking the area to 200-300 meters of depth, and then back to 400-500 meters. However, the area seems uplifted again to 200-400 meters later on in the Calabrian stage (1.25-0.97 Ma). Sedimentation of the Akrotiri deposits (NW Kephallonia Island, Ionian Sea), during the same chronostratigraphic interval, took place in a similar setting. At the Early Pleistocene (1.95-1.73 Ma) this basin reached depths of 400-450 meters, with uplift and following subsidence taking place between 1.73-1.66 Ma. Overall, the application of fish otolith paleobathymetry in the study areas provide a detailed picture of the depth variations for the Early Quaternary interval and refine the currently hypothesized pattern of tectonic movements.
Keywords: Teleosts; Eustacy; Tectonics; Sea-level fluctuations; Paleoceanography